The Role of Optical Radiations in Skin Cancer. (22nd April 2013) - Ayala, Fabrizio; Palla, Marco; Di Trolio, Rossella; Mozzillo, Nicola; Ascierto, Paolo A.
Abstract : Purpose . Electromagnetic radiation with wavelength in the range 100 nm to 1 mm is known as optical radiation and includes ultraviolet radiation, the visible spectrum, and infrared radiation. The deleterious short- and long-term biological effects of ultraviolet radiation, including melanoma and other skin cancers, are well recognized. Infrared radiation may also have damaging biological effects. Methods . The objective of this review was to assess the literature over the last 15 years and to summarize correlations between exposure to optical radiation and the risk of melanoma and other cancers. Results . There is a clear correlation between exposure to UV radiation and the development of skin cancer. Most importantly, a strong association between artificial UV radiation exposure, for example, tanning devices, and the risk of melanoma and squamous cell carcinoma has been clearly demonstrated. There is no clear evidence that exposure to IR and laser radiation may increase the risk of skin cancer, although negative health effects have been observed. Conclusions . Preventative strategies that involve provision of public information highlighting the risks associated with exposure to sunlight remain important. In addition, precautionary measures that discourage exposure to tanning appliances are required, as is legislation to prevent their use during childhood.